Impact of Admission Blood Glucose on Coronary Collateral Flow in Patients with ST-Elevation Myocardial Infarction - Ozge Kurmus; Turgay Aslan; Berkay Ekici; Sezen Baglan Uzunget; Sukru Karaarslan; Asli Tanindi; Aycan Fahri Erkan; Ebru Akgul Ercan; Celal Kervancıoglu (Cardiology Research and Practice)
In patients with acute myocardial infarction, glucose metabolism is altered and acute hyperglycemia on admission is common regardless of diabetes status. The development of coronary collateral is heterogeneous among individuals with coronary artery disease. In this study, we aimed to investigate whether glucose value on admission is associated with collateral flow in ST-elevation myocardial infarction (STEMI) patients. We retrospectively evaluated 190 consecutive patients with a diagnosis of first STEMI within 12 hours of onset of chest pain. Coronary collateral development was graded according to Rentrop classification. Rentrop 0-1 was graded as poor collateral development, and Rentrop 2-3 was graded as good collateral development. Admission glucose was measured and compared between two groups. Mean admission glucose level was 173.0 ± 80.1 mg/dl in study population. Forty-five (23.7%) patients had good collateral development, and 145 (76.3%) patients had poor collateral development. There were no statistically significant differences in demographic characteristics between two groups. Three-vessel disease was more common in patients with good collateral development (p=0.026). Mean admission glucose level was higher in patients with poor collateral than good collateral (180.6 ± 84.9 mg/dl versus 148.7 ± 56.6 mg/dl, resp., p=0.008). In univariate analysis, higher admission glucose was associated with poor collateral development, but multivariate logistic regression analysis revealed a borderline result (odds ratio 0.994, 95% CI 0.989–1.000, p=0.049). Our results suggest that elevated glucose on admission may have a role in the attenuation of coronary collateral blood flow in acute myocardial infarction. Further studies are needed to validate our results.